Corporate Governance in Financial Institutions - Spyros G. Stavrinakis; Christian Harm; David T. Llewellyn; Bridget Gandy; Peter Shaw; Peter Tebbutt; Mark Young (SUERF - The European Money and Finance Forum, 2007)
On 29th - 30th March 2007, SUERF and the Central Bank of Cyprus jointly organized a Seminar: Corporate Governance in Financial Institutions. The papers in the present publication are based on a sample of the presentations at the Seminar. Together, the papers illuminate a number of key issues in corporate governance in a variety of financial firms. In the first paper based on a keynote address, Spyros G. Stavrinakis, Central Bank of Cyprus gives an overview of the legal framework for corporate governance in financial institutions in Cyprus. According to a Central BankDirective issued in 2006, implementation of corporate governance principles is mandatory for all banks incorporated in Cyprus and their overseas branches and for some Cyprus branches of foreign banks domiciled outside the European Economic Area. Banks are obliged to have a robust internal governance framework, consistent lines of reporting and effective risk identification, management, monitoring and reporting procedures for all the risks to which credit institutions are actually or potentially exposed. The board of directors should take the lead in establishing and approving ethical standards and corporate values for itself and for the bank's senior executive management. Potential conflicts of interest should be identified, prevented or appropriately managed. Each bank should maintain a compliance function that monitors compliance with rules, regulations and policies. Clear lines of responsibility and accountability should be set and enforced. New members of the board of directors as well as the senior executive managers of banks have to be vetted and approved by the Central Bank of Cyprus for their " fitness and properness." In order to ensure transparency concerning the implementation of the principles, each bank's corporate governance framework should be disclosed in the bank's annual report and on its public website. In the second paper by Christian Harm, University of Muenster, "The Governance of the Banking Firm" the author builds on the literatures on corporate governance and financial regulation. In relation to governance of financial institutions, agency theory has both merits and shortcomings. It provides good explanations in many delegation situations but it has severe difficulties in dealing with institutions with several stakeholders and complex objective functions for the management. Firms guided by shareholder value may work more effectively than firms guided by stakeholder cacophony. Depositors are important stakeholders in banks. Since they are typically incapable of managing the supervision of their claims on the bank, they rely on regulators to do it for them. Remuneration systems for bank managers should provide proper incentives. According to the author, incentives should be structured such as to reward particular strategic achievements. Banks can apply executive stock option plans, but should confine options to a secondary place behind other long-term incentives based on success criteria that further shareholder interests without compromising the regulatory mission. Such an incentive framework tends, however, to be very complex so that the general ambiguities associated with the concept of governance could imply that in the banking firm, selecting managers with a proper intrinsic motivation may be superior to defining complex remuneration programs. In the third paper "Corporate Governance Issues in Non-Shareholder Value Financial Institutions: ACase Study of Mutual Building Societies in the UK", David T. Llewellyn, Loughborough University, focuses on corporate governance in non-incorporated financial firms. The author describes the relevant stakeholders and the nature of agency problems in different types of financial firms. He compares monitoring mechanisms, incentives, abilities and feasibilities of managers and members of mutuals. Mutuality raises specific corporate governance issues: Corporate governance is less clearly defined because the firm's objectives are less clearly defined. Conflicts of interest between managers and owners are less easily identified and it is more difficult to create management incentives. The almost exclusive source of capital is retained profits and each member has a non-exclusive and non-marketable claim to residual net worth. Voting rights are typically not proportional to the size of the ownership stake. There is no market in ownership claims and therefore no effective market in corporate control. Consequently, there is ample scope for mutuals to be inefficient. There is, however, no evidence that the efficiency and performance of mutuals are poorer that that of incorporated financial firms. In the fourth paper "Corporate Governance in Emerging Market Banks", Bridget Gandy, Fitch Ratings Ltd., and her co-authors from the rating agency look at the framework for corporate governance of banks in a sample of emerging market countries. Since the crisis in the late 1990s in Latin America and Asia, there has been a marked improvement in corporate governance of financial institutions in the regions under observation. Many countries have taken legal steps to develop functioning market economies with a view to the need to satisfy the demands of international capital markets. Several banks have listed their shares on stock exchanges in developed markets and foreign bank ownership and involvement in local banking systems have increased. In Central and Eastern Europe, countries' desire for EU-accession has impacted on the development of their corporate governance systems. At the individual bank level, Fitch Ratings looks at bank board independence and quality, oversight and the importance of related party transactions, the integrity of the audit process, acceptability of executive and director remuneration, ownership structures and transparency. In evaluating the quality of governance at the country level, the authors apply a three-pillar approach in line with Montesquieu: Powers and responsibilities need to be separated between a representative legislature, a competent and accountable executive branch and a fair and independent judiciary. The paper contains an interesting table in which a number of key regulatory initiatives in a sample of emerging market countries are compared. The authors point out that large scale privatizations have reduced the importance of state-owned banks in many countries. There are, however, still several examples with complex holding structures involving banks with potential negative implications for corporate governance quality and problems with related party transactions. Acquisitions by foreign banks with developed corporate governance standards have generally had a positive impact and also listing of bank shares on foreign stock exchanges with tough disclosure and transparency requirements have contributed positively to the quality of corporate governance in emerging market banks. Read together, the four papers give a good overview of the development of corporate governance practices and remaining problems in financial institutions of different types and with domicile in different countries.
Keywords: A13; D23; G00; G21; G34; G38; 330; Corporate governance; mutuals; shareholder rights; building societies; business objectives; Sarbanes-Oxley; Cyprus; central bank regulation; banking; directors; senior management; regulators; Corporate Governance; Bank; Großbritannien; Zypern; Europa; Schwellenländer; Welt